Networking against stakeholder risks: A case study on SMEs in international shrimp trade - Christian Dietsche (Belgeo)
The increasing internationalisation of business relations causes a multitude of risks for small and medium-sized enterprises. To reduce risks and uncertainties, it is of vital importance for these companies to build up and maintain network relations. In doing so, close and trust-based cooperation with suppliers, competitors or socio-political stakeholders can be established. However, the network effects are ambiguous: Typical network characteristics, such as mutual dependency, can easily turn out to be disadvantages and cause new risks. Drawing on stakeholder and network theory, this paper will take a closer look at how networks entail particular risks and determine the possibilities of corporate risk management. This will be illustrated with a case study of an environmentally sensitive value chain. The example of trade in shrimps between Bangladesh and Germany shows that shifting environmentally damaging production to developing or emerging countries does not protect European enterprises from environment-related risks.